Antimicrobial textile modified with silver nanoparticles in-situ synthesized using weed leaves extract - Ratnasari, Anisa (Environmental and Toxicology Management, 2021)
Silver nanoparticles (AgNPs) presence has considerable impact on microbial growth. In this paper, AgNPs was deposited on surface of four textiles to enhance the anti-microbial properties using immersion technique. Immersion technique was selected since it was simple, no need high energies, and no additional equipment required. In addition, AgNPs was synthesized using in situ-bio technique which is non-toxic, harmless and eco-friendly approach. Four textiles were evaluated, such as TA, TB, TC and TD. The finding projected that antifungal ability was correlated to the type of the textiles. TC textile has the significant antimicrobial activity with 12.33 ± 2.08 of inhibition zone which followed by TD (16.00 ± 3.46), TB (17.67 ± 7.09), and TA (17.67 ± 6.65). In addition, the surface bonding AgNPs on textile was possibility caused by the -OH group. It has a lone pair of electrons on the O atom that can interact with AgNPs to form –OAg bonds.